A PEDAGOGIA DO JORNALISMO NA TEORIA E PRÁTICA DE LUIZ BELTRÃO - Gurgel, Eduardo Amaral (2012)
The work describes and analizes the trajectory of Luiz Beltrão as one of the pioneers of the teaching of the journalism in Brazil, searching his didactic-pedagogic methodology. The goal is to reveal and characterize the constitution of the pedagogy of the communication by Luiz Beltrão made for the teaching of the journalism with his work and actions. It is presented in his midiologic bibliography, books which are truly manuals to the teaching of the journalism. For the achievement of this learning, it was used as methodology supports, the bibliographic search and documentary search, moreover, historic reconstructions with the intention of gathering data and qualifying information. The result of the search reveals that Luiz Beltrão forged a solid pedagogy made for the teaching of the journalism. It is concluded that his pedagogic action had an essential importance to the adjustment of the teaching of the journalism contributing to the production of the communication knowlegde in Brazil.